2016
DOI: 10.1002/ejic.201600991
|View full text |Cite
|
Sign up to set email alerts
|

The Key Heterolysis Selectivity of Divalent Sulfur–Sulfur Bonds for a Unified Mechanistic Scheme in the Thiosulfatolysis and Sulfitolysis of the Pentathionate Ion

Abstract: The thiosulfatolysis and sulfitolysis of pentathionate were studied in the pH ranges 4.50-8.0 and 4.0-5.0 at T = (25.0 ± 0.1)°C by HPLC monitoring of the time-dependence and distribution of different sulfur species. The two systems are first order with respect to both reactants. In contrast to tetrathionate, pentathionate and higher polythionates contain inequivalent divalent sulfur atoms; therefore, the complexity of the mechanism increases. The selective heterolytic cleavages of [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…However, our effort to synthesize solid potassium heptathionate with a purity higher than 90% has failed; therefore, peak areas of heptathionate were not converted into concentrations. In addition to this, it has recently been shown that during the course of thiosulfatolysis of pentathionate 25 turbidity of the reaction mixture appears at the beginning stage of the reaction and then it later disappears. In the case of the thiosulfatolysis of hexathionate because of the presence of γ and γ′-sulfur it is expected that this feature becomes more profound at the beginning stage, which may lead to the appearance of significant amounts of sulfur precipitation.…”
Section: ■ Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, our effort to synthesize solid potassium heptathionate with a purity higher than 90% has failed; therefore, peak areas of heptathionate were not converted into concentrations. In addition to this, it has recently been shown that during the course of thiosulfatolysis of pentathionate 25 turbidity of the reaction mixture appears at the beginning stage of the reaction and then it later disappears. In the case of the thiosulfatolysis of hexathionate because of the presence of γ and γ′-sulfur it is expected that this feature becomes more profound at the beginning stage, which may lead to the appearance of significant amounts of sulfur precipitation.…”
Section: ■ Resultsmentioning
confidence: 91%
“…Step R4 is the thiosulfate−sulfite group displacement equilibrium of pentathionate leading to the formation of hexathionate and sulfite studied first by Ji e al. 25 They were able to determine k R4 and k −R4 values as 0.0165 and 1050 M −1 s −1 , respectively. As it is seen, this reaction has to be a central part of our model as it must certainly be the initiating equilibrium when studying the hexathionate−sulfite reaction.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations